The English Literacy Subtest in Indonesia College Entrance Examination: A Bridge or a Barrier to Academic Reading? - Nurizqia, Rifania; Fitri, Auliana; Iasya, Lydia Kusdyanti; Wirza, Yanty (Universitas Jambi, Magister Program of English Education Department, 2026)
English literacy is one of the components of the National College Entrance Examination in Indonesia (SNBT), as it assesses students’ reading comprehension skills needed for academic study. This study explores students’ voices of the English literacy subtest, focusing on the difficulties they experience and their reflections on school-based English learning. A qualitative approach was employed, using questionnaires and semi-structured interviews with 32 first and second year students from a public university in Indonesia who had previously taken the SNBT. The findings show that students experienced different levels of difficulty across reading components. Linguistically, complex sentence structures required greater processing effort than vocabulary or grammatical features. At the comprehension level, identifying main ideas, understanding text organization, and restating information were perceived as more demanding than locating explicit details. Students also reported test-taking challenges, particularly post-review hesitation, confusing distractors, and lengthy reading passages. In reflecting on their school learning, students indicated that English instruction supported general reading comprehension and text understanding, but provided limited emphasis on strategic engagement with multiple-choice questions and inferential reading under test conditions. The study highlighted the need for alignment between classroom instruction and national assessment requirements for educators, curriculum developers, and policymakers in Indonesia.